Association of Genetic Variants of BMP4 with Type 2 Diabetes Mellitus and Clinical Traits in a Chinese Han Population. (18th November 2013) - Tang, Shanshan; Zhang, Rong; Yu, Weihui; Jiang, Feng; Wang, Jie; Chen, Miao; Peng, Danfeng; Yan, Jing; Bao, Yuqian; Jia, Weiping
Abstract : BMP4 is one of the transforming growth factor- β superfamily, which can participate in adipogenesis. Gene encoding BMP4 is acknowledged as a convincing candidate that may contribute to both glucose and lipid metabolism. In this paper, we aimed to test the impacts of BMP4 variants on type 2 diabetes in a large sample of Chinese population. We genotyped 10 tagging single nucleotide polymorphisms within the BMP4 region in 6822 participants and acquired detailed clinical investigations and biochemistry measurements. We found that BMP4 rs8014363 showed nominal association towards type 2 diabetes, with the T allele conferring a high risk of type 2 diabetes (OR = 1.108, 95%CI 0.999–1.229, P = 0.051 for allele; OR = 1.110, 95%CI 1.000–1.231, P = 0.050 for genotype), but it was no longer statistically significant after adjusting for multiple testing (empirical P = 0.3689 for allele based on 10, 000 permutations). Moreover, we observed a significant association of rs8014363 with triglyceride level and a trend towards association with high-density lipoprotein cholesterol after adjusting for age, gender, and BMI (P = 0.035 and 0.068, resp.). Our data suggested that the genetic variants of BMP4 may not play a dominant role in glucose metabolism in Chinese Han population, but a minor effect cannot be ignored.